2017
DOI: 10.4187/respcare.05245
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Oxygen Therapy: A Review and Update

Abstract: Oxygen is a colorless, odorless, tasteless gas that is utilized by the body for respiration. Oxygen has played a major role in respiratory care. Oxygen therapy is useful in treating hypoxemia but is often thought of as a benign therapy. After many years of study, we have learned a great deal of the benefits and potential risk of this powerful drug. Today oxygen gas is cheap, widely available, and easy to administer. Oxygen delivery devices vary in cost from a few cents for a simple nasal cannula to $25-$50 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 102 publications
(95 reference statements)
3
62
0
3
Order By: Relevance
“…Importantly, no respondents indicated that they used a scientifically validated method to ensure set flow was greater than or equal to the patient's inspiratory flow. Walsh and Smallwood 13 have put forth a method to approximate the initial flow setting for HFNC based on the patient's age and weight; to our knowledge, however, this method has not been validated in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, no respondents indicated that they used a scientifically validated method to ensure set flow was greater than or equal to the patient's inspiratory flow. Walsh and Smallwood 13 have put forth a method to approximate the initial flow setting for HFNC based on the patient's age and weight; to our knowledge, however, this method has not been validated in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the pain and discomfort caused to the fragile skin with constant pressure exerted on nose, cheeks and tapes used on face as a precaution to secure them. However, Walsh et al [2] opines otherwise in their review on these devices in view of the cost involved during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods of noninvasive oxygen delivery patterns for children include head box oxygen (oxy hood), free flow oxygen source held close to infants' nose, facemask, nasal prongs, nasal catheter and nasopharyngeal catheter [1]. Undoubtedly, oxygen therapy is an important tool that has saved many lives and improved others [2]. Monitoring oxygen saturation (SpO 2 ) is thus essential in order to decide course of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…4 It is used for treatment of many important causes of neonatal morbidity that result in hypoxemia, including respiratory distress syndrome, asphyxia, infection, and other primary lung diseases. 5 However, inappropriate use of oxygen therapy in neonates can also lead to serious adverse consequences. 6 In the post-World War II era, retinopathy of prematurity was a leading cause of blindness in Europe and North America, with unmonitored oxygen therapy as the major risk factor.…”
Section: Conclusion Onclusionmentioning
confidence: 99%